Prospective Analysis of a Sterile, Semi–automated Tissue Biopsy Homogenization Method in the Diagnosis of Prosthetic Joint Infections - SUREN, CHRISTIAN (In Vivo, 2017)
Background/Aim: Prosthetic joint infection (PJI) remains a serious complication of total joint arthroplasty. To effectively treat PJI, it is essential to identify the microorganism causing it and be able to combine correct surgical and anti-infective treatments. This cannot always be achieved with the currently employed diagnostic methods. The aim of this study was to evaluate a semi-automated tissue biopsy bead milling method (Ultra-TurrAX, Axonlab AG; Reichenbach, Germany) based on the hypothesis that the results are more sensitive for microbe detection and less prone to contamination. Materials and Methods: We included 35 consecutive patients undergoing 38 hip or knee arthroplasty revisions in this study. In addition to manually processed biopsies, we processed tissue specimens harvested intraoperatively using a semi-automated method. The sensitivity and specificity of both methods were calculated using MSIS criteria and sonication results as gold standards. Results: For total hip arthroplasty samples were evaluated separately based on MSIS criteria as the reference standard, Ultra-TurrAX processing yielded 81% (62-100%) sensitivity and 100% specificity. Using sonication as the gold standard, a sensitivity of 80% (60-100%) and specificity of 80% (45-100%) were calculated. In total knee arthroplasty, Ultra-TurrAX processing yielded 27% (1-54%) sensitivity and 57% (20-94%) specificity when using MSIS criteria as the gold standard. Using sonication as the gold standard, a sensitivity of 60% (17-100%) and specificity of 77% (54-100%) were calculated. Conclusion: This is the first study to analyze bead mill processing in total hip and knee arthroplasty revisions in a consecutive patient series. The method’s sensitivity was comparable to and its specificity superior to regular sample processing results reported in the literature with respect to hip arthroplasties and to both hip and knee arthroplasties collectively. With respect to total knee arthroplasties, the method fared worse in our collective, most likely due to the small number of patients in the sample. Integrating the method into the clinical workflow allowed for speedier and more efficient sample handling and processing. The theoretical advantage of a lower risk of contamination because of fewer manual processing steps is, in our opinion, valid.